الاعتبار الفقهي لحالة الاجتماع و حالة الانفراد - العشبي قويدر (University of Eloued جامعة الوادي, 2023)
إن لهذا الموضوع أهمية عظيمة في معرفة مقصود الشارع من اعتبار اجتماع الأوصاف وانفرادها في ترتيب الحكم الشرعي عليها ، و يدفع السائل إلى التشوف في معرفة أساس ذلك و هل له أثر في التطبيقات الفقهية ، و الهدف من هذا البحث وضع مدخل عام يسهل معرفة هذه القضية من خلال بيان حقيقتها و أساسها النظري و أثرها الفقهي . This topic is of great importance in knowing the purpose of the legislator to consider the combinations of descriptions and their unilateral in the judgments, and it prompts the questioner to know the basis of this, and does it have an effect on applications in the jurisprudence. The aim of this research is to create a prelude that facilitates understanding of this subject through its concepts, theoretical foundations and jurisprudence
Keywords: الاعتبار الفقهي; الاجتماع الإنفراد